Myopathy in Whipple's disease. Issue 10 (October 1977) - Swash, M; Schwartz, M S; Vandenburg, M J; Pollock, D J
Abstract : We report a patient with Whipple's disease who developed a myopathy that improved during antibiotic therapy. The muscle biopsy showed mild type 2 fibre atrophy, type 1 fibre preponderance, variability in fibre size, and changes in the myofibrillar pattern of affected fibres. Interfascicular macrophages contained PAS-positive material. With the electron microscope these macrophages contained membranous inclusions and bacillary bodies, similar to those seen in the jejunal biopsy.